The Time Delay Filtering Method for Cancelling Vibration on Overhead Transportation Systems Modelled as a Physical Pendulum - G. Peláez; J. Doval-Gandoy; N. Caparrini; J.C. García-Prada (Shock and Vibration)
An investigation of the response of a physical pendulum to time delay filtered inputs was conducted. It was shown that the physical pendulum model is more accurate than the simple pendulum for modelling the dynamic response of overhead cranes with loads hanging from hooks. Based on the physical pendulum model a Specified Time Delay filter for an experimental mini overhead crane was synthesized. While somewhat limited in the scope by the hardware conditions placed in the system, the results provide basic insights into the successful application of the Time Delay Filtering method to overhead cranes.